Artificial insemination of broiler breeder hens housed in individual cages - Resende, Osvaldo de Almeida; Santos, Maria Wanda dos; Dias, Paulo Genaro de Oliveira (Pesquisa Agropecuaria Brasileira, 2014)
Two hundred 24 week-old broiler hens, maintained in individual cages, were artificially inseminated once a week during four weeks with 0,05 ml of pooled semen, to evaluate the fertility and the residual effects of the increase in the energy level of the diet during the initial rearing period. The experimental design consisted of four groups, each consisting of 50 hens which had been fed until 35 days of age with one of the following diets: G. 1 - chick laying ration. G. 2- chick broiler ration. G. 3 - chick broiler ration plus 300 Kcal ME (metabolizable energy). and G. 4- chick broiler ration plus 400 Kcal ME The rates of fertility obtained were 88.9; 84; 88,3 and 87,8%, respectively, for treatment G.1, G.2, G.3 and G.4; and 93; 83,8; 87,2 and 85%, respectively, for the four periods. The differences between treatments and periods were nor statistically significant. The general fertility rate was lower than that generally obtained for laying hens reared under similar conditions. The increase in the energy level of the diet during the initial rearing period did not affect the fertility of the hens.